2021
DOI: 10.1016/j.celrep.2021.108800
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 drives invadopodia and interaction with mesothelial cells through ILK

Abstract: Endothelin-1 drives invadopodia and interaction with mesothelial cells through ILK Graphical abstract Highlights d ET A R/b-arr1 and ILK activate Rac3 GTPase, PAK1, and cofilin pathways through bPIX d ET A R/ILK/b-arr1/Rac3 regulates invadopodia, ECM proteolysis, and cell invasion d ET A R/b-arr1/ILK facilitates SOC/mesothelial cells interactions d Ambrisentan inhibits in vivo adhesion and metastatic spread of SOC cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…In addition, we found ILK expression was significantly associated with metastases of clinical specimens. And the association between ILK and cell survival and deterioration of ovarian cancer has also been reported before [ 63 – 67 ]. Although it has been demonstrated that the transcription of SNAIL1 can be regulated by ILK protein in certain cancers [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 61%
“…In addition, we found ILK expression was significantly associated with metastases of clinical specimens. And the association between ILK and cell survival and deterioration of ovarian cancer has also been reported before [ 63 – 67 ]. Although it has been demonstrated that the transcription of SNAIL1 can be regulated by ILK protein in certain cancers [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 61%
“…We previously demonstrated that the ET-1/ET A R axis in SOC cells facilitates adhesion and transmesothelial migration ( Masi et al, 2021a ). To investigate whether ET-1-induced MMT conversion might impact the transmesothelial migration of SOC cells, we used a co-culture system using fluorescent-labelled OVCAR3 cells and MCs previously cultured with or without ET-1 and/or BQ123 and BQ788.…”
Section: Resultsmentioning
confidence: 99%
“…An active ET-1 axis, involving the interaction with ET A R and ET B R, supports SOC growth and progression, and key signaling pathways activated by ET-1 related to invasion and metastasis are orchestrated by the cooperation of protein β-arrestins (β-arrs) with signaling proteins in cytosolic or nuclear compartments ( Rosanò et al, 2013 ; Peterson and Luttrell, 2017 ; Bagnato and Rosanò 2019 ; Tocci et al, 2019 ). Our recent studies addressing the question of how the ET-1 axis contributes to the reorganization of the cytoskeleton and cell motility during SOC metastatic progression uncovered a relevant role in invadopodia, F-actin-based protrusive membrane structures operating focused matrix degradation ( Masi et al, 2021a ). Acting as an anchoring point for players and signaling molecules regulating cell adhesion, invasion and proteolysis, β-arr1 determines the convergence of specific signal transducers ( Semprucci et al, 2016 ; Di Modugno et al, 2018 ; Chellini et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…S4A, B). Given that previous evidence describing the ability of ILK to promote YAP nuclear translocation [ 35 ] and because we have previously pointed out that ILK is downstream to the ET-1 signaling to promote OC cell invasive behaviour [ 7 , 9 , 36 ], we then investigated the involvement of this kinase in mediating the ET-1-induced YAP activity. IB analyses confirmed the capacity of ET-1/ET A R axis to upregulate ILK that was curbed by macitentan pre-treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%